PERAN POLRI DALAM MENGIMPLEMENTASIKAN RESTORATIVE JUSTICE PADA PENANGANAN PERKARA PIDANA (STUDI DI POLRES BINJAI) - Ronni Bonic; Alvi Syahrin; Marlina Marlina; Jelly Leviza (USU LAW JOURNAL, 2016)
ABSTRACT Restorative justice practices will be assessed on the dimension correlated with the enforcement of criminal law (law enforcement) conducted by the national police, for example correlated with the handling of cases handled by the fuction of detective in the investigation of crime. The framework used by the function of detectives in the investigation process that is based on a formal judicial or termination of criminal cases, the problems that arise are already fulfillment of the element of criminal elements when faced with problem resolution through restorative justice which takes precedence or ruled out, if embraced by the the community provided they are not contrary to the principles of criminal law. The role of the national police to implement restorative justice can not be separated from the rule of law is the basis for both the laws and regulations of the national police and the the national police internal policies that define the telegram letter head of the national police headquarters criminal detectives. Restorative implement justice carried out by national police detectives who carry out function basically intended for handling cases of children, common interests and the maintenance of social order.   Keywords : National Police, Restorative Justice, Criminal Cases Handling